Sensitivitas Pengasuhan Terhadap Kualitas Kelekatan Anak Buruh Migran - Hanisah, Baiq (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: Attachment is a mutual bond between mother and child that occurs in the earlydays of life and extends to other caregivers. Secure attachment is due to the interaction betweenthe child and significant caregivers. Secure attachment is useful for the development ofpsychological health, cognitive, emotional, and social development of a child. Replacement of themain caregiver (mother) to substitute caregiver affects the sensitivity of parenting that willultimately affect the quality of childâs attachment.Objective: To determine differences in the quality of attachment to children aged 3-5 yearsbased on substitute caregivers and to determine the relationship of parenting sensitivity to theattachment quality of migrant workersâ children in East Lombok District.Methods: This was an observational study with a cross sectional design with quantitativeapproaches. The independent variables were substitute caregivers and parenting sensitivity andthe dependent variable was quality of attachment. Parenting sensitivity was measured by makingobservations based on the Caregiver Interaction Scale and childâs attachment was measured byAttachment Q-Set (AQS). Based on total population sampling, the sample in this study was 136pairs of children and caregivers. The bivariable analysis used independent t-test and ProductMoment correlation test.Results: There was no difference in the child's attachment to his/her aunt and grandmother as asubstitute caregiver, but there was a positive relationship between parenting sensitivity ofsubstitute caregivers to childâs attachment. The child who was left at the age more than 24months had greater attachment 19.34% than that left at the age of less than or equal to 24months (with a coefficient of 24.21).Conclusion: There was no significant difference in child's attachment to grandmother and auntas a substitute caregiver; however, there was a relationship between parenting sensitivity ofsubstitute caregivers and childâs attachment. Keywords: Sensitivity, substitute caregiver, attachment, child and migrant workers